A Comparative Phytochemical Characterization of Moringa oleifera Plant Parts by Different Solvent Extraction - Sivapragasam, Gothai; Gokila Devi, T; Ragavan, Nanthiney Devi; Suryadevara, Nagaraja; Sridewi, Nanthini; Obaid, Sami Al; Alharbi, Sulaiman Ali; Arulselvan, Palanisamy (Indian Journal of Pharmaceutical Education and Research, 2024)
Background M. oleifera is an enriched plant with a variety of rich ingredients that play a very important part in the human diet. Thus, scientists have great interest in assessing the medicinal value of the plant to promote the preparation of new and advanced drugs. Hence, the preparation of plant extracts for experimental purposes is an initial step and key to achieving a quality research outcome. Materials and Methods The primary objective of this study was to evaluate the screening of M. oleifera bioactive compounds using various solvents (methanol, ethanol, acetone, petroleum ether, chloroform, and water) in the extraction procedure and determine the quality and quantity of bioactive constituents. Results The quantitative analyses showed that crude leaf, pod, and bark extracts revealed the presence of alkaloids, phenols, terpenoids, proteins, and carbohydrates in all extracts except for petroleum ether extract. Qualitative analysis of the detected phytochemicals reveals the highest concentrations were found in leaf extracts, where a high extraction yield was recorded in the aqueous extract. Conclusion This study reveals that the presence or absence of particular phytochemicals is determined by the polarity of the solvents used for extraction. Also, the justification for M. oleifera to contain rich phytochemicals, including alkaloids, flavonoids, phenolics, terpenoids, tannins, and saponins, that are known to have pharmacological properties, was validated, and they can be explored for biological potential.
Keywords: Moringa oleifera; Phytochemical; Antioxidant; Traditional medicine; Extraction yield